1994
DOI: 10.1055/s-2007-1001724
|View full text |Cite
|
Sign up to set email alerts
|

Short and Long-Term Effects of Growth Hormone Treatment on Lipid, Lipoprotein, and Apolipoprotein Levels in Short Normal Children

Abstract: Since recombinant growth hormone (GH) has been available, its use has been extended to treating not only children with growth hormone deficiency, but also short-statured children without GH deficiency. It is interesting, therefore, to determine whether GH therapy given in conventional doses causes metabolic side effects in these patients. In the present study we have examined the effect of recombinant human GH on eleven short normal children. Patients received 12 U/m2/week for 1 year. Before beginning treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…GH therapy did not change the total serum cholesterol, triglyceride, HDL-C, and LDL-C levels. These ®ndings are similar to those reported recently by Azzarito et al [2] in short normal children. No eect on the atherogenic index was demonstrated in our study in contrast with the results reported by Kohno et al [13] who found a decrease in the atherogenic index in boys with GHD who were treated with GH.…”
Section: Discussionsupporting
confidence: 93%
“…GH therapy did not change the total serum cholesterol, triglyceride, HDL-C, and LDL-C levels. These ®ndings are similar to those reported recently by Azzarito et al [2] in short normal children. No eect on the atherogenic index was demonstrated in our study in contrast with the results reported by Kohno et al [13] who found a decrease in the atherogenic index in boys with GHD who were treated with GH.…”
Section: Discussionsupporting
confidence: 93%
“…A decrease in TC and LDL-C was found in children with endogenous GH deficiency [20,26,27]. Contradictory results were obtained in 11 growth-retarded children without endogenous GH deficiency who were treated with rhGH for a year -TC and LDL-C increased at 6 months but remained within normal values and then decreased at 12 months [22]. Most studies in adults treated with rhGH showed decreased TC and LDL-C.…”
Section: Discussionmentioning
confidence: 92%
“…An increase in TG level during rhGH treatment was observed in adult patients without endogenous GH deficiency [21]. An increase in TG levels at 3 and 6 months, albeit within the normal range, was also found in 11 growth-retarded children without endogenous GH deficiency who received rhGH for a year [22]. Based on these data, it is difficult to draw any clearcut conclusions regarding the effect of rhGH on TG level.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study triglyceride levels were found to be elevated in treated rats significantly (P \ 0.01). Effects of GH on triglycerides could be due to an overproduction of VLDL-triglycerides by the liver, which in turn could be due to direct action of GH or a GH mediated increase in free fatty acids or insulin [18]. Lower activity of lipolytic enzymes may also be responsible for decreased triglyceride metabolism.…”
Section: Resultsmentioning
confidence: 99%